Epic meals: Who should read epic poetry in Rome? - Gellérfi, Gergő (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
In this paper, the presence of food and dinners in connection with epic poetry in three different Juvenalian poems is discussed. The first is Satire 4 containing a mock-epic, the plot of which revolves around a giant turbot that is described with epic-style elements, and that is given to the emperor Domitian characterized by uncontrolled gluttony. The other two poems, Satires 5 and 11, both focusing on dinner parties, are in connection with the epic genre as well: while in the closing poem of Book 1, several epic connotations appear in the description of the gluttonous Virro’s extravagant dinner, in Satire 11, the enjoyment of epic poetry is praised and compared to an almost pornographic dance performance in a luxurious feast. Reading the three poems together, it might be proved from another aspect that we have to make a distinction between the Juvenalian evaluation of topics described using epic-style elements and the epic poetry itself.